Reconstructing Islamic E-Business Ethics: A Maqashid-Based Framework For Ethical Decision-Making In Digital Markets - Johari Johari; Herdifa Herdifa; Dahri Ramadhan; Abdul Habib (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study addresses the growing ethical challenges in digital markets, including algorithmic manipulation, data exploitation, and deceptive interface design, which are not adequately covered by conventional Islamic business ethics. The research aims to develop a maqashid-based framework for ethical decision-making in Islamic e-business. This study employs a qualitative conceptual approach using literature review and maqashid al-shariah analysis to examine ethical issues in digital business practices. The findings reveal that existing Islamic ethical frameworks remain largely normative and lack operational mechanisms to address complex digital environments. In response, this study proposes a multi-layered maqashid-based framework that integrates foundational maqashid principles, ethical dimensions, application areas, and decision indicators. This framework transforms maqashid into an operational tool for evaluating digital business practices beyond formal compliance. The study contributes to the advancement of Islamic e-business ethics by offering a practical and context-sensitive model applicable to digital market systems.